Comparative analysis of mitogenomes among three species of Haplotropidini grasshoppers and a new species of the genus Sulcotropis (Orthoptera: Acridoidea: Pamphagidae) from China - Li, Xin-Jiang; Zhang, Da-Peng; Yin, Hai-Xiang (Zootaxa, 2020)
The complete mitochondrial genomes of three species of Haplotropidini were sequenced, annotated and analyzed. Then, combined with 18 species mitogenomes of Acridoidea and 1 species of Tridactyloidea, the phylogenetic relationships were reconstructed by maximum likelihood (ML) and Bayesian (BI) methods based on PCGs. The phylogenetic relationship tree showing that Sulcotropis Yin et Chou is a valid genus and not a synonym of Haplotropis Saussure, 1888. A new species Sulcotropis xiaowutaiensis sp. nov. is described in this paper from China, it is allied to Sulcotropis cyanipes Yin et Chou, 1979, but differs from latter by median carina of pronotum cut by posterior transverse sulcus slightly, epiphallus with middle part equal both sides in high, cercus of male gradually widened at base, interspace of mesosternum narrowed in the base slightly and subgenital plate of female oblong, hind margin with small acute angle in the middle. Type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, Hebei, China.